The relationship between job precariousness and student burnout: a serial indirect effects model. Issue 8 (17th November 2022) - Creed, Peter A.; Hood, Michelle; Selenko, Eva; Hu, Shi; Bagley, Louella
ABSTRACT: Much research has examined the association between precarious employment and wellbeing in adults, but little is known about this relationship in working students. Using a sample of 224 ( MAge 21 years; 68% female), we assessed self-perceptions of job precariousness across four domains (i.e., job insecurity, remuneration, conditions, flexibility) and tested the relationships between the four domains and student burnout, and whether these relationships could be explained sequentially by higher levels of job and financial strain and sleep disruption. Job insecurity alone related both directly and indirectly to burnout (via job and financial strain and poor sleep quality). Precariousness related to financial strain (insecurity, remuneration), job strain (insecurity, flexibility), and sleep quality (insecurity); financial and job strain related to sleep quality; and sleep quality related to burnout. By decomposing the job precariousness construct, the findings provide an improved understanding of how working in low quality, precarious jobs is related to student wellbeing.